The impact of Bis-GMA free and Bis-GMA containing resin composite as posterior restoration on marginal integrity: a randomized controlled clinical trial - Sara Ahmed Reda; Yasser Fathi Hussein; Mona Riad (BMC, 2023)
Abstract Background There have been concerns surrounding the utilization of Bis-GMA, a type of bisphenol A (BPA) derivative, within the dental industry. The aim of this study was to compare the performance of bulk fill Bis-GMA-free resin composite class II restorations in respect of its marginal integrity in comparison to bulk fill Bis-GMA-containing resin composite class II restorations over a 12-month period in a parallel clinical trial utilizing a split-mouth, double-blind, randomized strategy. Methods 20 patients participated in this study. Each patient has received one pair of class II posterior restorations, Bis-GMA-free (Admira fusion x-tra), and Bis-GMA containing (x-tra fil) on each side of the mouth (split-mouth strategy), (n = 40). The restorations' marginal integrity was evaluated based on Ryge's criteria (modified USPHS) at baseline (after 1 week), as well as 1 month, 3 months, 6 months, 9 months, and after 12 months of follow-up by two calibrated examiners. The statistical analyses utilizing the Friedman and Wilcoxon tests, the significance level was adjusted to 0.05. Results Following the 12-month period, all patients attended the recall visits to evaluate the restorations. The Wilcoxon signed-rank and Friedman tests, revealed that both types of bulk fill had 100% of Alpha (A) scores at baseline and after 1 month with no significant statistical differences. After 3, 6, 9, and 12 months, both tested bulk fill restorations showed Bravo (B) score with Bis-GMA free 10% and 5% for Bis-GMA containing with no statistically significant difference (p ≤ 0.05) for clinical marginal integrity parameter in USPHS criteria. Conclusions Bis-GMA-free resin composites demonstrated satisfactory, marginal integrity compared with Bis-GMA-containing resin composites within 12 months. Trial registration The protocol of the current study was registered at www.clinicaltrials.gov , with the identification number NCT05480852 on 29/07/2022. All procedures involving human participants were performed in accordance with the ethical standards of the Research Ethics Committee of the Faculty of Dentistry, Minia University, Egypt, under the approval number 419 on 27/06/2020.